Controlled trial of bowel rest in the treatment of severe acute colitis. - McIntyre, P B (1986)
In a prospective, randomised clinical trial, 47 patients with severe, acute, non-infective colitis treated with 60 mg intravenous prednisolone daily, received either bowel rest with parenteral nutrition or oral diet. Although those who received 'bowel rest' experienced a reduction in daily stool weight, there were no differences in the operation or mortality rates between the groups. Fourteen of the 27 patients with ulcerative colitis, but none of the 16 patients with Crohn's disease required urgent surgery. Bowel rest did not affect the outcome in severe ulcerative colitis treated with intravenous prednisolone. Ulcerative colitis and Crohn's colitis behaved differently in the acute attack.